N-(1H-Indazol-5-yl)-4-methoxybenzenesulfonamide - Hakima Chicha; El Mostapha Rakib; Latifa Bouissane; Mohamed Saadi; Lahcen El Ammari (Acta Crystallographica Section E, 2013)
In the title compound, C14H13N3O3S, the fused ring system is almost planar, the largest deviation from the mean plane being 0.023 (2) Å, and makes a dihedral angle of 47.92 (10)° with the benzene ring of the benzenesulfonamide moiety. In the crystal, molecules are connected through N—H...O hydrogen bonds and weak C—H...O contacts, forming a two-dimensional network which is parallel to (010).